2003
DOI: 10.1063/1.1592636
|View full text |Cite
|
Sign up to set email alerts
|

Strong photoluminescence and cathodoluminescence due to f–f transitions in Eu3+ doped Al2O3 powders prepared by direct combustion synthesis and thin films deposited by laser ablation

Abstract: In this letter, we report on fabrication and luminescent properties of phosphor powders and thin films of Eu3+ doped alumina Al2O3. The powders were fabricated by combustion synthesis process at a low temperature, 280 °C and showed strong photoluminescent and cathodoluminescent emissions. Powders of Eu3+ doped Al2O3 of concentration 1.0 mol % were deposited on quartz-glass substrates to form thin films by means of laser ablation. Under ultraviolet excitation and electron beam excitation, these samples containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…A literature survey of published luminescence spectra showed that our spectrum of ␣-Al 2 O 3 :Eu 3+ correspond to those from preparations using sol-gel techniques [12,15], except that materials annealed at 1100 • C in [18] produce spectra with broad features corresponding to amorphous phases. Also, the room temperature spectra of a 1% doped ␣-Al 2 O 3 film prepared by pulsed laser deposition [19], of a thin film prepared by laser ablation [20], and of a phosphor also produced by combustion synthesis [21] are in agreement with our results.…”
Section: Discussionsupporting
confidence: 89%
“…A literature survey of published luminescence spectra showed that our spectrum of ␣-Al 2 O 3 :Eu 3+ correspond to those from preparations using sol-gel techniques [12,15], except that materials annealed at 1100 • C in [18] produce spectra with broad features corresponding to amorphous phases. Also, the room temperature spectra of a 1% doped ␣-Al 2 O 3 film prepared by pulsed laser deposition [19], of a thin film prepared by laser ablation [20], and of a phosphor also produced by combustion synthesis [21] are in agreement with our results.…”
Section: Discussionsupporting
confidence: 89%
“…The 5 D 0 → 7 F 0 transition at ∼580 nm is theoretically forbidden due to the same total angular momentum, so it is always inexistent or much weaker than the 5 D 0 → 7 F 1 and 5 D 0 → 7 F 2 transitions [3][4][5][6][7]. However, in this paper, strong 5 D 0 → 7 F 0 transition of Eu 3+ ions in the ZnO:Eu films will be reported, and the related mechanism will be preliminarily explained.…”
Section: Introductionmentioning
confidence: 81%
“…It should be noted that the RE luminescent properties strongly depend on the symmetry around them. Eu-doped semiconductors (such as ZnO and GaN) [3,4] and insulators (such as Al 2 O 3 , Y 2 O 3 and SiO 2 ) [5][6][7] have been applied in thin-film electroluminescent devices [8], optoelectronic or cathodoluminescent devices [9] and telecommunications and lasers [10]. The popular routes to preparing ZnO:Eu films mainly belong to the chemical solution deposition, for example, spray pyrolysis [11] and sol-gel process [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Eu 3+ ions with S 6 symmetry, the 5 D 0 -7 F 1 magnetic dipole transition is dominant. The degree of site asymmetry is defined as the intensity ratio of the 5 D 0 -7 F 2 transition to the 5 D 0 -7 F 1 transition, the local symmetry of surrounding impurity ions, i.e., the occupancy ratio of the two different sites (ORS) could be obtained [18,61]. Fig.…”
Section: Luminescent Propertiesmentioning
confidence: 99%